Effective recruiting strategies : taking a marketing approach - Brounstein, Marth (Crisp Pub. Menlo ParkUS, 1992)
Teaches the market approach to recruiting; explains why it will work; how to spend less money attracting better recruits; and, how to spend less time and money finding the right recruit.\n